2022
DOI: 10.3390/genes13010144
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Haptoglobin Polymorphism on Stroke in Sickle Cell Disease Patients

Abstract: This review outlines the current clinical research investigating how the haptoglobin (Hp) genetic polymorphism and stroke occurrence are implicated in sickle cell disease (SCD) pathophysiology. Hp is a blood serum glycoprotein responsible for binding and removing toxic free hemoglobin from the vasculature. The role of Hp in patients with SCD is critical in combating blood toxicity, inflammation, oxidative stress, and even stroke. Ischemic stroke occurs when a blocked vessel decreases oxygen delivery in the blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Arboix et al [ 25 ] reported that patients who were young and had a prior history of venous thrombosis and recurrent stroke of undetermined cause were suspicious of hematological disease for stroke. Moreover, Hp 2 alleles are more disadvantageous than Hp1 alleles in sickle cell disease [ 26 ]. When considering that Hp is essential for reducing blood toxicity, oxidative stress, and inflammation in sickle cell disease, it is hypothesized that research on Hp is necessitated to find the clue and treatment for stroke, including ICH, in various hematologic diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Arboix et al [ 25 ] reported that patients who were young and had a prior history of venous thrombosis and recurrent stroke of undetermined cause were suspicious of hematological disease for stroke. Moreover, Hp 2 alleles are more disadvantageous than Hp1 alleles in sickle cell disease [ 26 ]. When considering that Hp is essential for reducing blood toxicity, oxidative stress, and inflammation in sickle cell disease, it is hypothesized that research on Hp is necessitated to find the clue and treatment for stroke, including ICH, in various hematologic diseases in the future.…”
Section: Discussionmentioning
confidence: 99%
“…DNA Template and Polymerase Chain Reaction (PCR) : PCR technique was used to amplify the haptoglobine gene according to 11 and used the following Primers for the PCR technique. Primers (forward and reverse) as the table (1) the kit provide by Geneaid Genomic DNA extraction Kit company(Taiwan). All samples were submitted to three reactions (1, 2 and 3) and the genotypes were defined after electrophoresis on 1.5% agarose gel and identification of the amplified fragment for each allele.…”
Section: Blood Collectionmentioning
confidence: 99%
“…Finally, the review entitled “Influence of Haptoglobin Polymorphism on Stroke in Sickle Cell Disease Patients” by Edwards et al is of substantial interest for our SI. This review outlines the current clinical research investigating how the haptoglobin (Hp) genetic polymorphism and stroke occurrence are implicated in sickle cell disease (SCD) pathophysiology [ 19 ]. Hp is an acute-phase protein capable of binding hemoglobin, thus preventing iron loss and renal damage [ 20 ].…”
mentioning
confidence: 99%
“…Hp is an acute-phase protein capable of binding hemoglobin, thus preventing iron loss and renal damage [ 20 ]. Edwards et al report the role of Hp in patients with SCD is critical in combating blood toxicity, inflammation, oxidative stress, and stroke [ 19 ]. IS occurs when a blocked vessel decreases blood-oxygen delivery to cerebral tissue and is commonly associated with SCD.…”
mentioning
confidence: 99%
See 1 more Smart Citation